PROSES PENGELOLAAN SURAT KELUAR DI KANTOR KEJAKSAAN NEGERI KABUPATEN BANDUNG - Patupi Rusyani, Puput; Yusuf, Ramayani; Nurcahya, Said Bambang; Yuliana, Pipit (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2024)
This study examines the management of outgoing mail at the State Prosecutor’s Office of Bandung Regency. The process is still handled manually, leading to delays, format inconsistencies, editorial errors, and unstandardized coding, which reduce efficiency. Using a qualitative descriptive method through observation, interviews with the Head of Administration, and documentation of workflow, the research found that the process involves drafting, checking, corrections, approvals, recording, and distribution. The main obstacles are repeated corrections, lack of thoroughness, and manual handling issues. The study concludes that the outgoing mail process remains vulnerable to errors and inefficiencies, requiring systematic improvements to ensure accuracy and timeliness.